Unacylated ghrelin does not alter mitochondrial function, redox state and triglyceride content in rat liver in vivo. (December 2015) - Gortan Cappellari, Gianluca; Zanetti, Michela; Semolic, Annamaria; Vinci, Pierandrea; Ruozi, Giulia; De Nardo, Margherita; Filigheddu, Nicoletta; Guarnieri, Gianfranco; Giacca, Mauro; Graziani, Andrea; Barazzoni, Rocco
Summary: Changes in liver mitochondrial function with more oxidized redox state and enhanced inflammation may contribute to the onset of obesity- and insulin resistance-associated hepatic complications, including non-alcoholic fatty liver disease and steato-hepatitis. Unacylated ghrelin (UnAG) is a gastric hormone reported to be associated with lower oxidative stress in different cell types, but its potential effects on liver mitochondrial function, redox state and inflammation in vivo remains undetermined. We investigated the impact of chronic UnAG overexpression (Tg Myh6/Ghrl) leading to systemic upregulation of circulating hormone on mitochondrial ATP production, redox state (oxidized-to-total glutathione) and inflammation markers in lean mice. Compared to wild-type animals (wt), Tg Myh6/Ghrl had superimposable liver weight, triglyceride content and plasma lipid profile. Liver mitochondrial enzyme activities and ATP production as well as oxidized-to-total glutathione were also similar in the two groups. In addition, no differences were observed in tissue inflammation marker TNF-alpha between wild-type and Tg Myh6/Ghrl animals. Thus, chronic systemic UnAG upregulation does not alter liver triglyceride content, mitochondrial function, redox state and inflammation markers in lean mice. These findings do not support a major role of UnAG as a physiological modulator of in vivo liver oxidative-lipid metabolism and inflammation.